Peranan Pemerintah Nagari dalam Penyelesaian Konflik Pengembangan Objek Wisata Pemandian Lubuak Soda, Nagari Tambangan Kabupaten Tanah Datar - Iffatul Ulya; Sinta Westika Putri (Lembaga Yasin AlSys, 2026)
Although nagari-based tourism development requires legal, participatory, and transparent governance, conflict resolution in the development of the Lubuak Soda bathing tourist attraction remains a challenge for the Tambangan Nagari Government. This study aims to analyze the role of the Tambangan Nagari Government in resolving conflicts related to the development of the Lubuak Soda bathing tourist attraction, identify the obstacles encountered, and describe the forms of conflict resolution pursued. This study used a qualitative approach with a descriptive case study design. The informants consisted of 11 people selected through purposive sampling, including the Nagari Head, the Nagari Customary Council, the Tourism Awareness Group, landowners, and the surrounding community. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the Miles and Huberman model. The results showed that the Tambangan Nagari Government performed roles as a stabilizer, direct implementer, pioneer, modernizer, and innovator in resolving conflicts related to tourism development. The most dominant role was that of stabilizer, which was realized through mediation, deliberation, appeals, and coordination among stakeholders. However, conflict resolution has not been optimal due to differences in interests, low trust, ineffective communication, limited authority of the nagari government, and the absence of binding regulations. These findings emphasize the importance of nagari regulations, governance transparency, and the involvement of all stakeholders in sustainable nagari-based tourism management. The implications of this study provide practical references for nagari governments and communities in strengthening participatory, legal, and socially and economically sustainable tourism conflict resolution mechanisms.